Angiogenin in the Neurogenic Subventricular Zone After Stroke - Marina Gabriel-Salazar; Ting Lei; Alba Grayston; Carme Costa; Esperanza Medina-Gutiérrez; Manuel Comabella; Joan Montaner; Anna Rosell (Frontiers in Neurology, 2021)
Ischemic stroke is a leading cause of death and disability worldwide with effective acute thrombolytic treatments. However, brain repair mechanisms related to spontaneous or rehabilitation-induced recovery are still under investigation, and little is known about the molecules involved. The present study examines the potential role of angiogenin (ANG), a known regulator of cell function and metabolism linked to neurological disorders, focusing in the neurogenic subventricular zone (SVZ). Angiogenin expression was examined in the mouse SVZ and in SVZ-derived neural stem cells (NSCs), which were exposed to exogenous ANG treatment during neurosphere formation as well as in other neuron-like cells (SH-SY5Y). Additionally, male C57Bl/6 mice underwent a distal permanent occlusion of the middle cerebral artery to study endogenous and exercise-induced expression of SVZ-ANG and neuroblast migration. Our results show that SVZ areas are rich in ANG, primarily expressed in DCX+ neuroblasts but not in nestin+NSCs. In vitro, treatment with ANG increased the number of SVZ-derived NSCs forming neurospheres but could not modify SH-SY5Y neurite differentiation. Finally, physical exercise rapidly increased the amount of endogenous ANG in the ipsilateral SVZ niche after ischemia, where DCX-migrating cells increased as part of the post-stroke neurogenesis process. Our findings position for the first time ANG in the SVZ during post-stroke recovery, which could be linked to neurogenesis.